UPAYA PENCEGAHAN JUDI ONLINE PADA USIA REMAJA - Cahya Utami, Okky Ambarita; Latifah, Eny; Utami Agustin, Indri Ati (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Online gambling is a criminal event that is rampant in the neighborhood, many of the perpetrators of this gambling act are children of immature age. The purpose of this research is as a countermeasure effort made by all parties so that the people around them stay away from online gambling. The literature method is characterized by direct contact with texts or manuscripts, its nature is ready to be used without the need to go anywhere because it is already available in the source, generally its nature is secondary sources, and is not limited by space and time. The research approach is a qualitative type of literature from the main source of the book Uncovering the Secrets of Online Gambling: Profits, Losses, and the Impact on Indonesian Society by Jengko Pigome and several previous studies on gambling. The results show that all elements of society, starting from oneself, family, community, to the government have a big role in preventing online gambling.